2014
DOI: 10.1007/s11032-014-0072-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the tomato yellow leaf curl virus resistance gene Ty-2 on chromosome 11 of tomato

Abstract: Resistances to begomoviruses, including bipartite tomato mottle virus and monopartite tomato yellow leaf curl virus (TYLCV), have been introgressed to cultivated tomato (Solanum lycopersicum) from wild tomato accessions. A major gene, Ty-2 from S. habrochaites f. glabratum accession “B6013,” that confers resistance to TYLCV was previously mapped to a 19-cM region on the long arm of chromosome 11. In the present study, approximately 11,000 plants were screened and nearly 157 recombination events were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 40 publications
2
84
0
1
Order By: Relevance
“…Ty‐2 is widely used by tomato breeders and there is some evidence suggesting that Ty‐2 enhances resistance of Ty‐3 (Yang et al. ) or Ty‐1 (Barbieri et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ty‐2 is widely used by tomato breeders and there is some evidence suggesting that Ty‐2 enhances resistance of Ty‐3 (Yang et al. ) or Ty‐1 (Barbieri et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Ty-2 has provided effective resistance to some begomoviruses in Taiwan and India (Hanson et al 2000), but it does not hold against bipartite begomoviruses. Ty-2 is widely used by tomato breeders and there is some evidence suggesting that Ty-2 enhances resistance of Ty-3 (Yang et al 2014) or Ty-1 (Barbieri et al 2010). Barbieri et al (2010) gave evidence on effectiveness specificity of Ty-1 and Ty-2 genes according to TYLCV-Is strains: Ty-1 and Ty-2 responded differently if challenged with two apparently similar viruses, that is TYLCV-Is and TYLCSV.…”
Section: Discussionmentioning
confidence: 99%
“…This gene family has been associated to different virus-resistance mechanisms. A MADS-box transcription factor was described as the Ty-2 candidate, involved in the tomato resistance to tomato yellow leaf curl virus (TYLCV) (Yang X. et al, 2014), and recently, a MADS-box gene has been reported to be upregulated in the Sw-7 resistance to tomato spotted wilt tospovirus (TSWV) (Padmanabhan et al, 2019). No SNPs with high-impact predicted effect were identified in CmoCh08G001760 between C. moschata accessions, but changes in 5 and 3 UTRs and a missense mutation with predicted moderate effect were polymorphic between resistant and susceptible accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a gene responsible for Ty1 resistance was identified as a DFDGD-class RNAdependent RNA polymerase and was demonstrated to be allelic with Ty3 resistance (Verlaan et al 2013). Ty2 resistance originated from S. habrochaites "B6013" and was recently mapped to a 300-kb interval on chromosome 11 (Hanson et al 2000;Ji et al 2009a;Yang et al 2014). Ty4 was identified on chromosome 3 as an additional resistance locus in Ty3-carrying S. chilense "LA1932" and "LA2779" (Ji et al 2009b).…”
Section: Tomato Yellow Leaf Curl Virus (Tylcv) Resistancementioning
confidence: 99%